Traumatic pure radiocarpal dislocation: a rare case report - Mutyala, Raviraj; Vutharkar, Nageswara Rao; Rajavali, Shahnawaz Hussain; Kunapareddy, Praveen Teja (International Journal of Research in Orthopaedics, 2026)
Radiocarpal joint dislocation is an extremely rare wrist injury, accounting for less than 1% of all traumatic wrist presentations. These injuries usually result from high-energy trauma and are frequently associated with severe ligamentous disruption, distal radioulnar joint (DRUJ) instability, or fractures. Early diagnosis and appropriate management are crucial to prevent long-term functional impairment. We report a case of a male patient who presented with severe wrist pain, swelling, and restricted movement one day following a road-traffic accident. Radiographic evaluation revealed dorsal radiocarpal dislocation (RCD) without associated fractures. Magnetic resonance imaging confirmed a pure ligamentous RCD with DRUJ instability. The patient was treated with closed reduction followed by percutaneous K-wire fixation of the radiocarpal joint and DRUJ. Immobilization was maintained for six weeks, after which progressive physiotherapy was initiated. At three-month follow-up, the patient was pain-free with significant improvement in wrist range of motion and grip strength. Follow-up radiographs demonstrated maintained radiocarpal alignment without evidence of subluxation or instability. Pure RCD is a rare but potentially disabling injury. Prompt diagnosis, early reduction, and appropriate stabilization are essential for favorable outcomes. Percutaneous K-wire fixation provides adequate stability in ligamentous injuries with persistent instability, while early rehabilitation is vital for optimal functional recovery.